Effect of alveolar recruitment maneuver on ischemia-modified albumin and oxidative stress in laparoscopic cholecystectomy - Zubeyir Cebeci; Betul Kozanhan; Huseyin Kurku; Sadik Ozmen (Medicine Science, 2019)
The effect of intraoperative recruitment maneuver on ischemia-modified albumin (IMA) and oxidative stress in performed laparoscopic cholecystectomy with intra-abdominal 12 mmHg pressure was investigated. Fifty patients undergoing laparoscopic cholecystectomy were included in the study by separating the two groups. Basal ventilator settings in both groups were set as tidal volume: 6-8 ml / kg, respiratory rate: 12 breaths / min, I: E = 1: 2, flow: 4 l / min. In group R, after intubation, 5 cm H2O PEEP was adjusted in addition to basal ventilator settings. Five minutes after CO2 insufflation and exsufflation, PEEP was step by step raised to 10-15-20 cm H2O, and patients were ventilated for 10 breaths. Venous blood samples were taken from the patients for three times in perioperative periods to measure IMA and oxidative stress.There was no difference between the groups in terms of demographic data, surgery and insufflation times. Significant differences in IMA,TOS,TAS and OSI levels within the group were observed but no difference was between groups. The recruitment maneuver that we used in laparoscopic cholecystectomies was found to have no effect reducing tissue ischemia and oxidative stress response in the intraoperative period. [Med-Science 2019; 8(2.000): 325-9]